Biological diversity: balancing interests through adaptive collaborative management - Buck, L.; Geisler, C.C.; Schelhas, J.; Wollenberg, Eva Karoline (CRC Press, 2001)
This book explores the use of adaptive collaborative management (ACM) as an approach to better balance local, national and global interests in conserving biodiversity with competing interests for resource use. ACM approaches resource management as an on-going learning process based on continuous, cumulative experimentation. This edited volume presents cases from around the world and interdisciplinary analyses to show how scientists, practitioners, policy makers and citizens can work together to achieve mutually agreeable outcomes.